Practices in Assessment for Learning in English Language Classrooms within Government Secondary Schools in Tanga City, Tanzania - Abdala, Jafari; Vuzo, Mwajuma (Papers in Education and Development, 2024)
This qualitative study investigated assessment practices in English language classrooms in six government secondary schools in Tanga City, Tanzania. Employing a case study design, the study involved 12 English language teachers and Form Three students. Specifically, the study aimed to identify assessment strategies employed by English language teachers, delineate the timing of assessments during instructional sessions and ascertain the language skills evaluated during the instructional process. The study findings revealed that teachers employ both oral and written assessment strategies. The finding also showed that assessment occurs systematically throughout all stages of lesson development. However, while writing skills and grammar received considerable assessment attention, speaking skills appeared to be relatively neglected. The study concludes by discussing its implications and highlighting a critical necessity for teacher training to enhance assessment literacy, particularly in assessing oral skills during instructional sessions. Keywords: Assessment for learning, communicative language teaching, secondary schools, classroom practice, Tanzania